2021
DOI: 10.7717/peerj.12125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune related cells and crucial genes in the peripheral blood of ankylosing spondylitis by integrated bioinformatics analysis

Abstract: Background Ankylosing spondylitis (AS) is a progressive rheumatic disease and studies reveal that the immune system is critical for the pathogenesis of AS. In the present study, various bioinformatics analysis methods were comprehensively applied, designed to identify potential key genes and inflammation states of AS. Methods The transcriptome profiles of GSE25101 and GSE73754 obtained from the Gene Expression Omnibus (GEO) database were merged for subsequent analyses. The differentially expressed genes (DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
6
11
1
Order By: Relevance
“…In this study, IL2RB and ZDHHC18 were the two finally screened hub genes. The former had already been identified by other researchers as one of the hub genes in AS (Zhu et al, 2013;Zheng et al, 2021), while to the best of our knowledge, the latter was first reported here by us. IL2RB, interleukin 2 receptor subunit beta, encoded the beta subunit of a heterodimer or heterotrimer receptor involved in T cell-mediated immune responses and is probably involved in the stimulation of neutrophil phagocytosis by IL15 (Ratthé and Girard, 2004; Frontiers in Genetics frontiersin.org Zhang et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…In this study, IL2RB and ZDHHC18 were the two finally screened hub genes. The former had already been identified by other researchers as one of the hub genes in AS (Zhu et al, 2013;Zheng et al, 2021), while to the best of our knowledge, the latter was first reported here by us. IL2RB, interleukin 2 receptor subunit beta, encoded the beta subunit of a heterodimer or heterotrimer receptor involved in T cell-mediated immune responses and is probably involved in the stimulation of neutrophil phagocytosis by IL15 (Ratthé and Girard, 2004; Frontiers in Genetics frontiersin.org Zhang et al, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…In this study, IL2RB and ZDHHC18 were the two final screened hubgenes. The former had already been reported by other researchers to be one of the hubgenes in AS [30,31], while the latter was first reported here by us.…”
Section: Discussionsupporting
confidence: 79%
“…CD247 is commonly defectively expressed in autoimmune diseases compared with healthy individuals, and its specific role and mechanisms are less studied compared with SLE (Table 1). The expression of CD247 in rheumatoid arthritis (RA), 70 paediatric primary nephrotic syndrome, 71 systemic sclerosis (SSc), 72 juvenile idiopathic arthritis, 73 osteoarthritis 74 and ankylosing spondylitis 75 patients is decreased compared with healthy people 76 and increased in patients with type 1 diabetes mellitus (T1DM) 77 . CD247 was downregulated in peripheral blood mononuclear cells, T cell subsets in synovial fluid and NK cells in RA patients, and CD247 mRNA expression levels were significantly lower in a highly active group compared to inactive RA patients 68 .…”
Section: Cd247 and Autoimmune Diseasesmentioning
confidence: 99%